2009
DOI: 10.1177/1721727x0900700304
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutation Detection of Regulatory Molecule Dopamine Gene Receptors (D1–D5) Encoding Analysis on Human Peripheral Blood Lymphocytes in Schizophrenia Patients

Abstract: There is much evidence which highlights the involvement of the dopamine system in the pathophysiology of schizophrenia. Recently, there have been reports of detected mutations in dopamine gene receptors in genomic DNA of schizophrenia. In this study, we attempt to determine whether there is mutation in encoding dopamine receptor. The PBMC was separated from whole blood by Ficoll-hypaque; the total cellular RNA was extracted and the cDNA was synthesized. This process followed by real-time PCR using primer pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Psychological therapy is an approach that is being used by adults with cancer to manage a spectrum of treatmentrelated symptoms and facilitate the process of psychological readjustment to the loss, change, and uncertainty characteristic of cancer survivorship (39)(40)(41)(42)(43)(44)(45). With advances in early diagnosis, treatment, and long-term management of cancer, the number of people living with metastatic and advanced cancers has continued to grow worldwide.…”
mentioning
confidence: 99%
“…Psychological therapy is an approach that is being used by adults with cancer to manage a spectrum of treatmentrelated symptoms and facilitate the process of psychological readjustment to the loss, change, and uncertainty characteristic of cancer survivorship (39)(40)(41)(42)(43)(44)(45). With advances in early diagnosis, treatment, and long-term management of cancer, the number of people living with metastatic and advanced cancers has continued to grow worldwide.…”
mentioning
confidence: 99%
“…PBMCs were isolated by a density gradient medium (Lymphoprep) and treated with APO, as shown in Figure 1. PBMCs express dopamine receptors and dopamine transporters and also synthesize dopamine through tyrosine hydroxylase-dependent mechanisms [91,92]. PBMCs total RNA from patients with alcoholism (n: 24) and controls (n: 17) was extracted using TRIZOL.…”
Section: The Functional Relationship Of Ankk1 and Drd2mentioning
confidence: 99%
“…These cytokines orchestrate the recruitment and activation of different effector cells, such as eosinophils and mast cells (35). These cells, along with Th2 cytokines, are key players in the development of chronic allergic inflammatory disorders, usually characterized by airway hyperresponsiveness, reversible airway obstruction, and airway inflammation (36). Accumulating evidence has shown that altering cytokine-producing profile of Th2 cells by inducing Th1 responses may be protective against Th2-related diseases such as asthma and allergy (37).…”
mentioning
confidence: 99%